Diversity of reef fish species in presence of mangrove habitat in Ternate, North Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Utama RS, Renyaan J, Nurdiansah D, Makatipu PC, Suyadi, Hapsari BW, Martha E, Rahayu EMD, Sugiharto A. Akbar N. 2022. Diversity of reef fish species in presence of mangrove habitat in Ternate, North Maluku, Indonesia. Biodiversitas 23: 5184-5193. Research on reef fish has been widely reported, where information about reef fish communities is an important factor for evaluating fisheries management and coral reef management. Mangroves as the nursery, foraging, and growing areas were also important to assure sustainable reef fish fisheries. This paper studies reef fish abundance and diversity in Ternate Waters in the presence of mangrove in coral reef habitats. To determines coral reef condition underwater photo transect was performed while an underwater visual census (UVC) was used to determine the abundance and diversity of reef fishes in Ternate waters between 2017 and 2018. A total of 14 stations were used, with eight stations near the mangroves and six stations that did not contain mangroves. Based on the observation, fish species richness in mangrove absence was higher than in the presence of mangroves, with 68 and 65 species in 2017 and 66 and 62 species in 2018. However, the abundance of reef fish was recorded high in the presence of mangroves than in the absence of mangroves, with 390 and 289 individual differences in 2017 and 2018. Mangroves' complexity affected part of reef fish communities in Ternate water, particularly Lutjanidae, Serranidae, and Scaridae, which might influence the abundance of reef fishes rather than the species richness. In addition, carnivore shows a negative effect in the presence of mangroves, in contrast with herbivores. It is related to mangrove functioning as a temporary shelter when high-pressure presence in their natural habitat (reef) and a place for foraging. Therefore, mangrove management must be a consideration in the coral reef or fisheries management program.
Keywords: reef fish, mangroves, abundance, diversity, management